Multifeature Fusion Method with Metaheuristic Optimization for Automated Voice Pathology Detection - Özbay, Erdal; Özbay, Feyza Altunbey; Khodadadi, Nima; Gharehchopogh, Farhad Soleimanian; Mirjalili, Seyedali (Elsevier Inc., 2024)
Voice pathologies occur due to various factors, such as malfunction of the vocal cords. Computerized acoustic examination-based vocal pathology detection is crucial for early diagnosis, efficient follow-up, and improving problematic speech. Different acoustic measurements provide it. Executing this process requires expert monitoring and is not preferred by patients because it is time-consuming and costly. This paper is aimed at detecting metaheuristic-based automatic voice pathology. First, feature maps of 10 common diseases, including cordectomy, dysphonia, front lateral partial resection, contact pachyderma, laryngitis, lukoplakia, pure breath, recurrent laryngeal paralysis, vocal fold polyp, and vox senilis, were obtained from the Zero-Crossing Rate, Root-Mean-Square Energy, and Mel-frequency Cepstral Coefficients using a thousand voice signals from the Saarbruecken Voice Database dataset. Hybridizations of different features obtained from the voices of the same diseases using these three methods were used to increase the model's performance. The Grey Wolf Optimizer (MELGWO) algorithm based on local search, evolutionary operator, and concatenated feature maps derived from various approaches was employed to minimize the number of features, implement the models faster, and produce the best result. The fitness values of the metaheuristic algorithms were then determined using supervised machine learning techniques such as Support Vector Machine (SVM) and K-nearest neighbors. The F1 score, sensitivity, specificity, accuracy, and other assessment criteria were compared with the experimental data. The best accuracy result was achieved with 99.50% from the SVM classifier using the feature maps optimized by the improved MELGWO algorithms. © 2024 The Voice Foundation
Keywords: Grey Wolf Optimizer; MELGWO; MFCC; RMSE; Voice pathology; ZCR